LA ΣKHNH EN LOS FRAGMENTOS TRÁGICOS ANTERIORES A LA ORTESTÍA - Librán Moreno, Myriam (Myrtia, 2002)
The σκηνή-building in the fragments of tragic authors before the Oresteia (458 BC). This paper is concerned with the oftendenied existence of the σκηνή-building before ca. 458 BC. as evidenced by the fragments of tragedies and satyr plays written before that date and by vascular paintings dealing with early dramas.